In vivo quantification and pharmacokinetic studies of cotinine in mice after smoke exposure by LC–MS/MS. (29th December 2019) - El Mubarak, Mohamed A.; Danika, Charikleia; Cachon, Charlyne; Korovila, Charalambia; Atsopardi, Korina; Panagopoulos, Nikolaos; Margarity, Marigoula; Poulas, Konstantinos; Sivolapenko, Gregory B.
Abstract: A sensitive analytical method was developed and validated for the quantification of cotinine in mouse plasma after exposure to smoke of 0.5, 1.0, and 1.5 commercially available cigarettes, using liquid chromatography tandem mass spectrometry. The method was validated over a linear concentration range of 0.075–20.0 ng/mL with the R 2 value being higher than 0.99. Both the precision (coefficient of variation; %) and accuracy (relative error; %) were within acceptable criteria of <15%. The lower limit of quantification (LLOQ) for cotinine was 0.075 ng/mL with sufficient specificity, accuracy, and precision. Following exposure to 0.5, 1.0, and 1.5 cigarette smoke, it was observed that the AUC and the C max increased linearly as the doses increased. The pharmacokinetics of cotinine was found linear for the range of 0.5–1.5 commercial cigarette smoke. The quantification of the concentration of cotinine in mouse plasma after smoke exposure will facilitate future behavioral and toxicological experiments in animals and may prove useful in predicting cotinine levels in humans during smoking.